Circular Economy and ESG – A European Perspective for Sustainable Development and Mitigation of Climate Change Effects - Florin Bonciu (Romanian Journal of European Affairs, 2023)
This research presents, from two perspectives (the global perspective and the European Union’s), the urgency of fighting climate change as an essential element for achieving sustainable development. In this context, it explores the synergy between two concepts that are usually approached separately: circular economy and ESG (environmental, social, governance). This synergy and its benefits are set forth in the larger scope of the 2030 strategy of the United Nations for Sustainable Development Goals. Within this framework, an assessment of the EU’s leading role (in supporting and implementing ESG and circular economy) showcases that, in the past quarter century, the European Union has become a supplier of valuable solutions for sustainable development and a catalyst for the rest of the world in the mitigation of climate change effects.